Pertumbuhan Bawang Merah (Allium ascalonicum L.) Lokal Samosir Pada Berbagai UkuranWadah dan Dosis NPK - Hendri Tawar Miko Lubis; Jonis Ginting (Talenta Publisher, 2018)
The aims of the research were to study the influence of various size containers and doses of NPK fertilizer on the growth of the shallot. The research was conducted in the greenhouse of Agriculture Faculty, University of Sumatera Utara, Medan, which began from Oktober 15th – October 28th, 2017. The research was arranged by using randomized block design with 2 factors, i.e; size containers 15 cm, 20 cm, 25 cm, and 30 cm and the dose of NPK 0 g, 0.5 g, 1 g, 1.5 g, and 2 g. The parameters observed were plant length, number of leaves and number of tillers. The results showed that all parameters observed were not significantly affected by size container, a dose of NPK and interaction between both treatments until the age of 14 days after planting.